2023
DOI: 10.1101/2023.01.14.524047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypometabolism to survive the long polar night in the diatomFragilariopsis cylindrus

Abstract: Diatoms, the major eukaryotic phytoplankton in polar regions, are essential to sustain Arctic and Antarctic ecosystems. As such, it is fundamental to understand the physiological mechanisms and associated molecular basis of their resilience to the long polar night. Here, we report an integrative approach revealing that in prolonged darkness, diatom cells enter a state of quiescence associated with reduced metabolic and transcriptional activity during which no cell division occurs. We propose that minimal energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Surviving decades of dormancy implies the need for active cell maintenance such as DNA repairs to maintain cell viability, prevent microbial degradation and allow future regermination. The requirement of active cell maintenance has previously been suggested to be essential due to cell deterioration during dormancy (Joli et al, 2023; Sciandra et al, 2022). Previous studies of gene expression performed on resting spores of the diatom Chaetoceros socialis have suggested that cellular activities during dormancy is mostly dependent on internal recycling of substrates (Pelusi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Surviving decades of dormancy implies the need for active cell maintenance such as DNA repairs to maintain cell viability, prevent microbial degradation and allow future regermination. The requirement of active cell maintenance has previously been suggested to be essential due to cell deterioration during dormancy (Joli et al, 2023; Sciandra et al, 2022). Previous studies of gene expression performed on resting spores of the diatom Chaetoceros socialis have suggested that cellular activities during dormancy is mostly dependent on internal recycling of substrates (Pelusi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, S. marinoi survives dark, cold, and highpressure conditions and degrades its own photopigments to meet dissimilatory and/or assimilatory demands. External stress factors are known to induce autophagy of cellular components in diatoms 48,49 . Even at highest pressure levels, however, the cellular contents of photopigments remained substantial, which makes them suitable biomarkers even in the deep ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a more likely explanation is lipid metabolism by the diatoms themselves, assuming that they survive the pressure treatment. Stressed diatoms are known to sacrifice membrane lipids for TAG production to feed minimal dark respiration activity under prolonged darkness 49 . TAGs are then shuttled as lipid droplets into the vacuole where they will be degraded 48 .…”
Section: Discussionmentioning
confidence: 99%
“…As confirmed by nile red staining, the cellular lipid pool is depleted after 10 months of dark inception, where only <1% of the cellular volume remained occupied by lipid droplets in all 5 strains. Drawing energy from the lipid pool via autophagy or lipophagy during darkness was also suggested for the polar diatom Fragilariopsis cylindrus (Joli et al, 2023). Another source for energy in benthic diatoms can be anaerobic respiration using intercellular storage pools of NO 3 to reduce them to NH 4 (Kamp et al, 2011).…”
Section: Membrane Integrity Differs Between Marine and Limnic Strainsmentioning
confidence: 99%